Implementasi Power Line Communication (PLC) untuk Monitoring Penggunaan Arus di Politeknik Negeri Malang - Galuh Lukitasari; aad hariyadi; Ridho Hendra Yoga Perdana (Jurnal Jaringan Telekomunikasi, 2018)
One of the communication technologies that can be used for monitoring current usage is communication technology via electric grids or what is called Power Line Communication (PLC). The advantages of this technology are that the electricity network is already distributed in each building so there is no need for new installations, it is economical and affordable in terms of economics, and is more practical and flexible in its use. In this study, a current usage monitoring system using PLC is proposed which will be applied in every class in the AI ??building of Malang State Polytechnic. The sensor that will be used in measuring the current value is the current sensor SCT-013. By using the KQ330 PLC module as a PLC transmission modem. The implementation of PLC which is applied in each class in the AI ??building has a BER (bit error rate) value of 0.012 in the experiment of sending 1000 data with an error of 12 times at the farthest distance of approximately 15 meters. And have a BER value of 0 or have no error in sending data at the closest distance of approximately 2-5 meters. In this study, the process of sending and receiving data using Power Line Communication allows it to be done at a distance that is not too far away to avoid excessive data errors.